PENGARUH MINAT BELAJAR DAN PRESTASI PESERTA DIDIK TERHADAP PERUBAHAN KURIKULUM DI SEKOLAH DASAR ISLAM RAMAH ANAK KECAMATAN CILODONG KOTA DEPOK - Siti Suryanih (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Curriculum change is not merely administrative but must reflect the evolving needs and characteristics of students. Therefore, this study focuses on how learning interest and student achievement influence the direction and nature of curriculum changes in child-oriented Islamic elementary education settings. The purpose of this study is to determine the extent to which learning interest and student achievement affect curriculum changes implemented in Ramah Anak Islamic Elementary Schools in the Cilodong Sub-district. This study employs a quantitative approach with a survey technique. The sample consists of 15% of the population, totaling 85 respondents selected using purposive sampling. The research instrument used was a closed-ended questionnaire with a Likert scale. The research findings indicate that students’ learning interest significantly affects curriculum change, as does academic achievement. Both variables simultaneously contribute positively to the dynamics of the implemented curriculum. The conclusion of this study is that learning interest and student achievement are two critical factors that must be considered in the curriculum change process at Ramah Anak Islamic Elementary Schools. An effective curriculum should be designed based on the actual needs of students. Therefore, the results of this study can serve as a basis for policy-making at the school and educational institution levels to support more meaningful and sustainable learning.